RECURRENT NASOPHARYNGEAL CARCINOMA: PROBLEM AND MANAGEMENT - Hayati, Rusina (TALENTA PUBLISHER, 2020)
Abstract Introduction: Treatment results for nasopharyngeal carcinoma (NPC) have been improved, but there were still some patients who developed localized persistent or local recurrent. Local recurrence still represents a major cause of mortality and morbidity also management still challenging issues. Case Report: A 27-year-old woman presented with bilateral conductive hearing loss, dysphagia, rhinorrhoea, epistaxis, and cranial nerve palsy after chemo radiation for NPC. The results of nasopharyngoscopy, CT scan, and PET scan were not found a mass in the nasopharynx. The result of nasopharyngeal biopsy result was undifferentiated carcinoma. Patient diagnosed with recurrent NPC and planned for re-radiotherapy. Conclusion: After complete treatment for NPC we must immediately ensure recurrence and choose the next appropriate treatment.